Evaluating the role of spatial planning and environmental impact assessment in facilitation environmentally appropriate development : the case of the Big Bay development in Blaauwberg, Cape Town - Aaron, Samuel (Department of Environmental and Geographical Science, 2014)
This dissertation assesses the roles of spatial planning and Environmental Impact Assessment (EIA) in informing appropriate development in the case of the Big Bay development. The roles considered are those that relate to the planning of the biophysical environment. The dissertation further assesses how the roles relate to the nature of the relationship between the processes followed by the two disciplines. The study found out that planning and EIA had essential roles in informing the development. The roles of EIA related to the identification of environmental issues while those of planning related to the incorporation of those environmental issues into the development proposal. The nature of the roles related to the levels at which the two disciplines were applied and the manner in which they related. EIA was applied at the project level long after the decision to develop the site was made. EIA was thus not used to evaluate the development alternatives so as to identify the development that was suitable for the Big Bay bio-physical environment. The proponents of Strategic Environmental Assessment (SEA) argue that SEA is best placed to inform the selection of appropriate development. Planning was applied at various levels and, thus, it was involved at both the strategic level and the project level. At the strategic level, planning attempted to identify environmental issues but could not go beyond obvious physical features like dune systems and the coast. At the project level, planning relied on EIA for the identification of environmental issues for incorporation into development proposals. Throughout the planning process, the Big Bay site was sub-divided into smaller precincts with guidance from the EIA on environmental issues. At the lowest level of planning including Site Development Planning (SDP), however, many precincts were so small that the EIA did not identify any new environmental issues - each precinct was either entirely suitable for conservation or development. Planning and EIA related in a series of coordinated interactions. The dissertation associates the interactions with integration and mutual adjustment. In their interaction, planning and EIA mutually adjust to each other. On several instances, the two disciplines had to compromise their positions to facilitate consensus in decision making. In the case study it was found that the two coordinated so well and the flow and incorporation of information was successful. The flow of information was done in time and the information influenced the outcomes of each process.